Competitors take note: how China manages its tech skills resources. Issue 4 (12th June 2018) - Marshall, Anthony; Qu, Lucy; Yang, Po; Zaharchuk, Dave; Zhan, Ying
Abstract : Purpose: The research article looks at how well China is managing its tech skills resources in major industries. Design/methodology/approach: The IBM Institute for Business Value in collaboration with Oxford Economics recently conducted a specific survey of more than 5, 600 global business, government and education leaders on the topic of global workforce skills. More than 400 of the 5, 600 executives surveyed were from China, representing 18 specific industries from across all major regions. The insights and opinions of these 400-plus Chinese executives inform this report about tech skills resources in China. Findings: Seventy-one percent of corporate recruiters in China, say they cannot find applicants with sufficient practical experience, and 72 percent of the Chinese industry leaders surveyed report that gaps evidenced in the core skills of newly recruited employees is the single most significant business challenge they face. Research limitations/implications: The interviews were performed in 2016 and the data analyzed in 2017 and 2018. Practical implications: Seventy-one percent of Chinese executives believe that individuals should bear significant personal responsibility in developing and maintaining work skills. Originality/value: This is a large sample of executives in major Chinese corporations and some representatives of Chinese educational institutions. Their insights about China's talent gaps and what it is doing on many fronts to modernize its talent resources should be of interest to players in all competitive economies.